Reasons for requesting cone-beam computed tomography in children and adolescents: a 10-year study - Akleyin, Ebru; Eskibaglar, Busra Karaagac (Taylor & Francis Ltd, 2022)
Analysis of the reasons for requesting dental cone-beam computed tomography (CBCT) in children and adolescents can provide new evidence to guidelines developed specifically to protect patients from potential harmful effects of ionizing radiation. This retrospective study aimed to determine the reasons for requesting dental CBCT in paediatric patients. We included all patients aged <18 years who underwent CBCT between 2011 and 2021 at the Dentomaxillofacial Radiology Department of Dicle University Dental Faculty. Out of 8214 archived records in total, 1619 CBCT request forms of paediatric patients were examined. These forms provided the data on each participant's age, gender, requesting department, the reason for the request, and year of the request. We evaluated 762 males and 857 females; 0.68% were aged 4-5 years, 27.55% were 6-11 years, and 71.77% were 12-17 years. The requests for CBCT were made by the Orthodontics Department in 61.4% of cases and by the Surgical Department in 25.82% of cases. The most common indication for CBCT (33.42% of cases) was to determine the presence of embedded teeth. We found a significant correlation between the age group and indications (p < 0.05). The age group of children and adolescents for whom CBCT was requested most often was the 12-17 years age group. In conclusion, the most common indication for CBCT was to determine the presence of embedded teeth in orthodontics. The rate of use of CBCT in the diagnosis and treatment of paediatric patients in dentistry has increased in the last decade.
Keywords: Paediatric dentistry; three-dimensional imaging; cone-beam computed tomography